The Comparison of Students’ Mathematical Problem Solving Ability through Students Teams Achievement Division (STAD) and Problem Based Learning (PBL) - Chairuddin Chairuddin; Farman Farman (STAI Hubbulwathan Duri, 2022)
The purpose of the study was to determine the comparison of students’ mathematical problem-solving abilities through STAD and PBL learning models. This research was an experimental study with a nonequivalent post-test only control group design. The population of this study were all grade IX students of SMP Negeri 1 Kolaka for the 2018/2019 academic year, which consisted of eight classes totalling 200 students. The sample selection was done by using cluster sampling technique so that two classes IXD were obtained class IXD as the class that used the STAD model and class IXA as the class that used the PBL model. Class IXD has 25 students, and IXA has 26 students. The research data was collected through documentation, observations, and a problem-solving ability test. The research data in this study were analyzed using descriptive and inferential statistics. The results showed that descriptively the mathematical problem-solving ability (MPSA) of students in the STAD and PBL learning models showed an average score of 70 (good) and 69.34 (enough). Inferentially from the prerequisite test, the data obtained were normally distributed, and the variance of the two data was homogeneous. The hypothesis was tested using an independent sample t-test. The results of hypothesis testing indicate that there was no significant difference between students' MPSA with the application of the STAD learning model and the PBL model. So it was concluded that there was no difference in students' mathematical problem-solving abilities in using the STAD learning model or the PBL model.